(untitled) (Iranian Journal of Kidney Diseases, 2012)
A young boy with prior constipation developed recurrent severe calcium phosphate kidney calculi, sometimes sufficient to cause acute kidney failure and hydronephrosis. After several major surgeries, food allergies were determined by serum immunoglobulin E testing, and when he finally went on a gluten-free diet, he stopped forming calculi and has had no surgeries related to kidney calculi since. Hyperoxaluria was not identified in this child by 24-hour urine analysis, unlike most other reports of kidney calculus formation in individuals with gluten intolerance.